Chronicles of an announced heterotopia: Municipal urban renovation program, Tacna avenue Extension, Rímac district, 1986 - Chunga Gómez, Hilda Katherine (2022)
The uncontrolled expansion of the city, the exclusion of the sectors with lower incomes from public policies, the accelerated increase in housing prices, the overcrowding and progressive detriment of the built heritage in the Historic Center of Lima and the limitations of the state apparatus as facilitator and subsidiary of private initiatives, generated the necessary context to implement projects and programs focused on improving the housing infrastructure in Metropolitan Lima. In this sense, this article analyzes the case of the “Urban renewal program of the properties located in the Extension of Av. Tacna, 1986”, conceived as a response to the slum problem of the Historic Center of Lima, which despite not being fully realized, provides the inputs to have greater clarity regarding the complexity of the execution of each of the components of an urban renewal program where the building, the political and the social are intertwined in a complex, polysemic and changing system in time, in a heterotopia as Foucault would define it